Kahoot Utilization! To Support Game-Based Learning - Nor Ainah Rusliana; Susanti Sufyadi; Qomario Qomario (Publikasi Indonesia, 2024)
The use of Kahoot in today's digital era is increasingly important in supporting an interactive and fun learning process. As a gamification-based learning platform, Kahoot allows educators to create quizzes and challenges that are accessible online, increasing student engagement and facilitating active learning. So this research aims to explain the use of Kahoot! to support Game-Based Learning. The method used in this study uses the SLR (Systematic Literature Review) method using the Preferred Reporting Items for Systematic Reviews and Meta-analyses method commonly called PRISMA. The results of the 11 articles used in this review literature show that activeness in the learning process makes learning interactive and interesting and becomes one of the learning media options for teachers. Conclusion After studying the use of Kahoot in ICE, interest arose in the potential of this platform in supporting learning through gamification. Kahoot creates interactive learning experiences with real-time quizzes and challenges, which increases student engagement. Research shows that the platform makes the learning atmosphere competitive and fun, and provides live evaluation for teacher feedback. Thus, Kahoot can motivate students and improve academic outcomes.